If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 29 + -9n = 4n + 3 Reorder the terms: 29 + -9n = 3 + 4n Solving 29 + -9n = 3 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 29 + -9n + -4n = 3 + 4n + -4n Combine like terms: -9n + -4n = -13n 29 + -13n = 3 + 4n + -4n Combine like terms: 4n + -4n = 0 29 + -13n = 3 + 0 29 + -13n = 3 Add '-29' to each side of the equation. 29 + -29 + -13n = 3 + -29 Combine like terms: 29 + -29 = 0 0 + -13n = 3 + -29 -13n = 3 + -29 Combine like terms: 3 + -29 = -26 -13n = -26 Divide each side by '-13'. n = 2 Simplifying n = 2
| 7p+9q=22 | | (4c-1)(5c-3)= | | 87+2x=5x | | 2y-3+4x=45 | | 6(p-1)-p=-2(p+1)+p-1 | | 6s-2=4s+6 | | 18=m-6 | | 4(x-1)+2(2x-3)=12-x+3(3-x) | | 4y-6x=36 | | 11x^2-4x+2=0 | | 4x+1=9x-20 | | 2ac^2+ac=b^2+3b | | 2(x-8)-(x-4)=3(x+5)+3 | | b^2+3b=4b^2 | | 3r+10=5r+2 | | 0.273y-18.3=.36-2.7y | | X^2-28=12x | | 0.723y-183=0.36-2.7y | | x^2+49y^2=0 | | x+4/4-2x-1/2=x-2/4 | | 2(2x+5)=3(x+3) | | 5x+221=13x-11 | | 6y+21=4y-4 | | x^2+49y^2=64 | | 168-7x=38x+18 | | x^2+49y^22=64 | | 168-7x=38+18 | | 8x+8(3x+10)=32 | | 12-7x=30+21x | | x+(x*.088)=20 | | 10x-12=78 | | 2q+12=5q+3 |